Foreign Language Reading Anxiety Among Indonesian EFL Senior High School Students - Muhlis, Azhari (ENGLISH FRANCA : Academic Journal of English Language and Education, 2017)
This study aims to investigate foreign language reading anxiety among Indonesian EFL Senior High School students. Thirty two students of grade eleven in a senior high school in Bandung were involved as the participants. This study employed a survey research design. The primary data source was collected by two types of questionnaires and the secondary data source was gained by interview. The findings revealed that most of the students perceived anxiety in medium level (71,9%). The study found that there were two major potential factors of foreign language reading anxiety namely text features and personal factors. Under the concept of text features, there are three sources of foreign language reading anxiety including unknown vocabulary, unfamiliar topic, and unfamiliar culture. Unknown vocabulary was considered as the most potential factor of reading anxiety under the aspect of text features (49%). On the other hand, under the concept of personal factors, there are two sources of foreign language reading anxiety including afraid of making errors, and worry about reading effects. Afraid of making error was nominated as the highest potential factor of reading anxiety under the aspect of personal factors (39%). Implication to the study and recommendations for further research were considered. Keywords: Foreign language reading anxiety, potential factors of foreign language reading anxiety